Grazing Management Concepts and Practices - L.E. Sollenberger; J. Vendramini; J. Dubeux; M. Wallau (EDIS, 2018)
Grazing management can be defined as the manipulation of livestock grazing to accomplish a desired result. The desired result depends upon the enterprise, but for most producers economic goals are of primary importance. Decisions regarding what grazing management to use are based on the characteristics of the forage being grazed, animal requirements, input costs associated with adopting a particular system, and the probability of return on investment.